SERUM LEVELS OF 2MICROGLOBULIN AND SOME BIOCHEMICAL PARAMETERS AMONG CHRONIC HEPATITIS B PATIENTS - Al-Shaikle, Maysoon K (Al-Nahrain Journal of Science, 2010)
The aim of this study was to estimate the level of 2microglobulin (B2M), total serum bilirubin(TSB) and alanine aminotransferase (ALT) in the sera of (30) chronic hepatitis B (CHB) patients(patients group) and (30) healthy HBV carriers as (control group). The study showed that levels of2 microglobulin were high among patients group (3.41 1 mg/L), while it was normal amongcontrol group (1.42 0.35 mg/L). Regarding biochemical parameters, it was found that (TSB) and(ALT) were increased among patients group, and their level were (37.66 30.8 mol/L) and(43.6 32.51 U/L) respectively. While it was normal among control group (4 0 mol/L) and(17.4 7.16 U/L) respectively.